2017
DOI: 10.20849/ijsn.v2i1.146
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Parent-Adolescent Communication, Acculturation, and Sexual Knowledge on Latino Adolescent Sexual Behavior: A Systematic Review

Abstract: Latino adolescents in the United States are more likely to engage in early and risky sexual behavior compared to adolescents from other racial and ethnic groups. The quantity and quality of parent-adolescent sexual communication has been suggested as the best predictor on adolescent sexual behavior. Method: A systematic literature review of studies was conducted with relationships between selected parental, adolescent and cultural variables and Latino adolescents' intentions to engage in sexual behavior, deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The parent–adolescent dyad about communication on relationships and sexual health has become a contemporary public health issue as studies have shown it is effective in setting a solid foundation for an adolescent to have good sexual health and sexual behavior. 4 , 5 Over the last few years, sexual activity around the globe has been on a steady rise among the adolescent population, 6 , 7 which makes Adolescent Sexual Reproductive Health (ASRH) a global Public Health issue.…”
Section: Introductionmentioning
confidence: 99%
“…The parent–adolescent dyad about communication on relationships and sexual health has become a contemporary public health issue as studies have shown it is effective in setting a solid foundation for an adolescent to have good sexual health and sexual behavior. 4 , 5 Over the last few years, sexual activity around the globe has been on a steady rise among the adolescent population, 6 , 7 which makes Adolescent Sexual Reproductive Health (ASRH) a global Public Health issue.…”
Section: Introductionmentioning
confidence: 99%